BURKITT’S LYMPHOMA - Ahmad, Shakeel; Hussain, Altaf; zaman, Sharif -u- (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT: A case of Burkitt’s Lymphoma is reported here in a patient who had disuse swelling of the mandible and right maxilla. It almost obliterated the buccal cavity and invaded the orbits resulting in bilateral proptosis and blindness.